Answer:
1 seconds
Explanation:
The number of seconds till the frog back on the ground is as follows:
Let us assume the h be the height of the frog
And, the t is the time
Given that
![h = -6t^2 + 6t](https://img.qammunity.org/2022/formulas/mathematics/high-school/tee6l6asp6rglq4ayl7keg5i8ykmhj6mnc.png)
Here we assume at the ground the h = 0
So,
![0 = -6t^2 + 6t](https://img.qammunity.org/2022/formulas/mathematics/high-school/6j8wl183nyvr8h5exhbyjpwvnpkx0kc3vh.png)
Now divide by 6
![0 = -t^2 + t\\\\0 = t(-t + t)\\\\t = 0 \\\\0 = -t + t\\\\t = 0 \\\\ t = 1](https://img.qammunity.org/2022/formulas/mathematics/high-school/zx8p4057q9b5ibl49gbrqawrive51hxgaw.png)
So for getting back to the ground it comes back in 1 seconds